The language of yin : yoga themes, sequences & inspiration to bring your class to life & life to your class - Harris, Gabrielle (Yoga teacher) ([Luminary Press], 2019)
'The Language of Yin' is more than a book on themes. It is a comprehensive guide to becoming the type of teacher that inspires and moves people beyond the skin and bones. Starting with some proven techniques for teaching, the book moves into setting the beginning scenes to connect students to their practice. The book then presents over 40 universal themes that will provide inspiration for both you and your students. Long after the poses have faded, the students will remember how you made them feel using the descriptive and connected language provided. Each class has three categories; mind, heart and body. These categories define, embellish and connect the poses to the heart and soul, making the themes relatable and exciting.